Dermatoglyphic palmar pattern variations in congenitally deaf and mute subjects - Bansal, Rimple; Goyal, Ruchi; Chhabra, Usha; Kaur, Harsimarjit; Kalyan, Gurdeep Singh (International Journal Of Community Medicine And Public Health, 2024)
Background: Dermatoglyphics have the unique merit of retaining all their peculiarities unchanged throughout life, and afford in consequence an incomparably surer criterion of identity than any other bodily feature. The rationale for studying dermatoglyphic features is derived from the fact that development of dermal ridges and congenital deafness seems to develop at around the same time. Methods: The material for the study consisted of palm prints of congenitally deaf and mute children of 100 subjects with congenital deafness and muteness between 5-21 years of age and 50 control of similar age group with normal hearing and speech were chosen. The principal patterns of thenar/ I interdigital, interdigital II, interdigital III, interdigital IV and hypothenar area were noted. Position of axial triradius, ‘atd’ angle, pattern of palmar Flexion Creases, presence as well as pattern of the Simian Line and the Sydney Line were recorded. Results: The percentage of open field was maximum in subjects in thenar / interdigital area I. and in interdigital area IV. The mean a-b, c-d and atd angle ridge palmar ridge count was less in subjects in comparison to controls. Highly statistically significant results were obtained between subjects and control for the simian crease pattern when both hands were considered together in which the percentage of transitional type was more than the typical simian crease in subjects. Conclusion: When combined with other clinical and investigative features, dermatoglyphic study can serve as a diagnostic impression and can be advocated as a useful screening device.